The Concept of Partnership Supervision by The Indonesia Competition Commission and Legal Effort - Gunawan Widjaja (IHSA Institute, 2022)
A partnership is a form of cooperation between micro, small and medium enterprises with large businesses which can be misused. For this reason, it is necessary to supervise the partnership agreement. The institution appointed to carry out supervision is the Indonesia Competition Commission (KPPU). This study was made with the aim of examining the concept of partnership supervision by the Indonesia Competition Commission (KPPU) and the legal remedies that can be taken in relation to the supervision carried out by KPPU. This research is normative legal research, which uses secondary data. The secondary data used is based on primary legal sources consisting of a series of applicable laws and regulations. The analysis was conducted qualitatively in order to examine the existing legal norms more deeply and comprehensively.